2005
DOI: 10.1163/157338205774661825
|View full text |Cite
|
Sign up to set email alerts
|

Reconsidering the Hooke-Newton Debate on Gravitation: Recent Results

Abstract: The second half of the seventeenth century is populated by such towering protagonists of the Scientific Revolution as

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…1 Some authors write that the assumption of an inverse relation between gravity and the square of the distance was common by the time Newton published his Principia Mathematica [8][9][10] where m 1 , m 2 , and G are the masses of the first and second objects, and Newton's gravitational constant respectively. Let us compare this equation to that of the force between two electrically charged objects, given by Coulombs law…”
Section: Gravity and Its Relation To Gauge Theoriesmentioning
confidence: 99%
“…1 Some authors write that the assumption of an inverse relation between gravity and the square of the distance was common by the time Newton published his Principia Mathematica [8][9][10] where m 1 , m 2 , and G are the masses of the first and second objects, and Newton's gravitational constant respectively. Let us compare this equation to that of the force between two electrically charged objects, given by Coulombs law…”
Section: Gravity and Its Relation To Gauge Theoriesmentioning
confidence: 99%
“…In the Principia (1687), Isaac Newton was eventually able to synthesize terrestrial and celestial physics by adopting a consistent representation of space for all scales. He was motivated by Robert Hooke, who had sought to prove that a force proportional to the inverse square of the distance to the sun would generate the orbital dynamics described by Kepler's laws of planetary motion (Gal 2002;Guicciardini 2005). Significantly, in considering the problem, Hooke employed an oriented representation of space and the principle of rectilinear inertia.…”
Section: Representations Of Space In the Early Modern Periodmentioning
confidence: 99%
“…(Guicciardini 2005) The mathematician and philosopher Newton seemed to many colleagues what Glanvill called a "dogmatist" who "betrays poverty and a narrowing of the spirit," and being "too confident in opinion," showing ""ill manners and immodesty." (Guicciardini 2005) (Bechler 1974) Due to Pugliese's works and the interpretations offered by Michael Nauenberg, Hooke has now been re-evaluated as a good mathematician. (Pugliese 1989) (Nauenberg 2005) Hooke can be understood, as Gal pointed out, only by placing his work on planetary theory in the broad context of his multiple interests.…”
Section: What the Supporters Of Robert Hooke Saymentioning
confidence: 99%
“…During the second half of the seventeenth century there was a plethora of thinkers of the Scientific Revolution, such as Robert Boyle, Christiaan Huygens, Robert Hooke, Isaac Newton, Gottfried Wilhelm Leibniz, etc., starting many controversies about intellectual property and disputes about the scientific priority on new discoveries and concepts. (Guicciardini 2005) The modern theory of gravity began with the work of Galileo Galilei, with his famous experiments of the balls falling from the tower of Pisa and left to slip on an inclined plane. He found that gravity is the same for all objects, the differences occurring only due to different resistances to the air during the fall.…”
Section: Introductionmentioning
confidence: 99%